2019
DOI: 10.1186/s13036-019-0186-z
|View full text |Cite
|
Sign up to set email alerts
|

A silkworm based silk gland bioreactor for high-efficiency production of recombinant human lactoferrin with antibacterial and anti-inflammatory activities

Abstract: Background Silk glands are used by silkworms to spin silk fibers for making their cocoons. These have recently been regarded as bioreactor hosts for the cost-effective production of other valuable exogenous proteins and have drawn wide attention. Results In this study, we established a transgenic silkworm strain which synthesizes the recombinant human lactoferrin (rhLF) in the silk gland and spins them into the cocoon by our previously constructed silk gland based biore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Studies revealed that some pigments found on the yellow Nangnoi silk (Thai silk) are associated with the presence of carotenoids and flavonoids [7,8]. The phenolic compounds are well-known for antioxidant activity as well as some biological functions such as anti-hypertensive [9], antiviral [10], antioxidant [11], antibacterial, and anti-inflammatory activities [12]. Dutta et al [13] reported that the antioxidant potential of the edible insect Vespa affinis L. could mediate its therapeutic activities in oxidative stress-associated health disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed that some pigments found on the yellow Nangnoi silk (Thai silk) are associated with the presence of carotenoids and flavonoids [7,8]. The phenolic compounds are well-known for antioxidant activity as well as some biological functions such as anti-hypertensive [9], antiviral [10], antioxidant [11], antibacterial, and anti-inflammatory activities [12]. Dutta et al [13] reported that the antioxidant potential of the edible insect Vespa affinis L. could mediate its therapeutic activities in oxidative stress-associated health disorders.…”
Section: Introductionmentioning
confidence: 99%
“…We previously constructed a transgenic silkworm strain that could specifically produce silk cocoons with rhLF distributed in its sericin layer (Figure 1A). 34 Via rearing this transgenic silkworm strain and letting the silkworm do the hard work, we could harvest (timeand cost-effectively) silk fiber with functional rhLF at a large scale; thus, the shortage of the rhLF resource could be solved well. Sericins from WT and rhLF silks were extracted using 8 M urea buffer to fabricate sericin hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…Fabrication of Silk Sericin Hydrogel Loaded with rhLF. Wild-type (WT) and rhLF silk cocoons were obtained by rearing a WT or rhLF silkworm strain 34 and wild type silkworm strain (D9L) using fresh mulberry leaves or artificial diet, and the two types of cocoons were stored at room temperature before use. Extraction of sericin was performed as previously reported with some modification.…”
Section: Experimental Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory diseases such as neurodegenerative illness, inflammatory bowel disorder, dermatitis, pulmonary diseases, and arthritis have been shown to stimulate Lf. Furthermore, Lf treatment has been demonstrated in most animal experiments to reduce experimental inflammation in such organs 102 . For instance, Lf prevents chemical and IL-1β -driven cutaneous inflammation in humans and animals, chemically induced inflammatory bowel disease in rats and mice, nonsteroidal anti-inflammatory drugs (NSAIDs)-induced colon damage in rodents, and inflammation in a rat model of rheumatoid arthritis 103 .…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%